Sakrifisi dan Algoritmanya: Sebuah Catatan Propadeutis tentang Rasionalitas Sakrifisial Penciptaan Nilai - Bawono, B. Haryo Tejo (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2024)
The word ‘sacrifice’ is both admirable and repulsive. It can be a “desired value” or a “crime against humanity”. Unfortunately, our ancestors left sacrifice theories unresolved. This paper will demonstrate that analyzing and reinterpreting sacrifice texts and theories yields a “sacrificial algorithm.” This term ‘algorithm’ means methodological, not mechanical. This article delves into the economical logic behind sacrifice after examining different concepts and theories on the subject. To address this issue, this article proposes an alternative understanding of both sacrifice and the economy. A change in perspective on sacrifice allows people to recognize its capacity to generate inherent values. Sacrifice can be viewed as a rational response in an irrational world. This allows us to consistently return our lives and lived-experiences to the original meaning of sacrifice, sacra facere, to make something (or some act) sacred.